Answer:
Explanation:
Let the initial money deposited in the account be x:
If he added $54 to the amount he started with in his account, the expression will become:
x+54
If the sum is tripled, we will have:
3(x+54)
Since the balance an-mount is $381, the final equation will give:
3(x+54) = 381
The equation that represents the situation is 3(x+54) = 381
Next is to calculate x:
3(x+54) = 381
open the parenthesis
3x+162 = 381
3x = 381 - 162
3x = 219
x = 219/3
x = 73
Hence the original amount in his account is $73